Dynamics of the 4D genome during in vivo lineage specification and differentiation - A. Marieke Oudelaar (Nature Portfolio, 2020)
The relationship between regulatory elements, chromatin interactions and gene expression during development remains poorly understood. Here the authors present Tiled-C, a low-input 3C approach to study genome architecture at high resolution, and apply it to mouse erythroid differentiation in vivo, finding that enhancer-promoter interactions are formed gradually during differentiation, concomitant with progressive upregulation of gene activity.